Strict social distancing measures helped early control of SARS-CoV-2 spread in Duhok city, Iraq - Nawfal R Hussein; Ibrahim Naqid (Journal of Infection in Developing Countries)
The aim of this letter is to discuss the pandemic management measures, including social distancing and community containment, taken in Duhok city in Northern Iraq, where a few patients were infected with COVID-19. During the first three months of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, 15 patients were diagnosed with SARS-CoV-2 in Duhok city. All the patients were asymptomatic and were discharged to their home within 10 ± 3.2 days after throat swabs indicated a negative SARS-CoV-2 Real Time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) test. The social distancing and lockdown measures taken by the city were implemented in three stages. In the first stage, all educational institutions including schools, colleges and universities were closed. In the second stage, all gatherings were banned. Finally, state-imposed community-wide containment was declared. The social distancing measures helped control infections in the city. Gradual reopening is recommended to avoid the spread of infection.